2006
DOI: 10.1111/j.1478-4408.2006.00006.x
|View full text |Cite
|
Sign up to set email alerts
|

Functionalisation of lyocell. Part 1: Amination of lyocell with m‐phenylenediaminesulphonic acid derivatives

Abstract: A series of four colourless, water‐soluble agents, based on m‐phenylenediaminesulphonic acid, and designed to aminate lyocell, have been synthesised. Each agent carried one or two aromatic amino groups ortho to a water solubilising sulphonic acid group, together with one or two electrophilic groups. The electrophilic groups studied were dichlorotriazinyl, monochlorotriazinyl, vinylsulphonyl and triazinyl betaine. The agents were applied to lyocell by padding techniques, and neutral‐exhaustion dyeing of the ami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
5

Year Published

2013
2013
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
0
1
0
5
Order By: Relevance
“…But there are some disadvantages which make it difficult to apply to industrial production; for instance, the high production cost, the health and safety of industrial production, the repeated pollution, and the degradation of wearability. 15,16 The epichlorohydrin-dimethylamine polymer is an ecofriendly cationic polymer. It was reported that this cationic polymer could be synthesized by two-step polycondensation, whose weight-average molecular weight was less than 10 000 g mol.…”
Section: Introductionmentioning
confidence: 99%
“…But there are some disadvantages which make it difficult to apply to industrial production; for instance, the high production cost, the health and safety of industrial production, the repeated pollution, and the degradation of wearability. 15,16 The epichlorohydrin-dimethylamine polymer is an ecofriendly cationic polymer. It was reported that this cationic polymer could be synthesized by two-step polycondensation, whose weight-average molecular weight was less than 10 000 g mol.…”
Section: Introductionmentioning
confidence: 99%
“…Devido a elevada reatividade, acrescida de instabilidade da ligação estér, a modificação química por esterificação apresenta limitações como método a aplicar à funcionalização da celulose [87]. Assim, a imobilização de aminas na celulose clorada é mais adequada do que por esterificação, quando se quer obter aminas ligadas diretamente à celulose.…”
Section: Esterificação Da Celuloseunclassified
“…A 2-aminoetilcelulose, pode ser preparada por reação da celulose com soluções aquosas alcalinas de compostos como 2-cloroetilamina (Figura 18), ácido aminoetilsulfurico (Figura 19) e etilenoimina [87].…”
Section: Eterificação Da Celuloseunclassified
See 2 more Smart Citations